Cloud computing strategies - Chorafas, Dimitris N. (CRC Press/An Auerbach Books, 2011)
A guide to managing a cloud project, this book illustrates how to take advantage of cloud computing and align it with business and IT strategies. It assesses cloud computing technologies and demonstrates how to determine requirements and implement cloud to meet the goals and objectives of IT and business